High‐Pressure Synthesis of Sc5P12N23O3 and Ti5P12N24O2 by Activation of the Binary Nitrides ScN and TiN with NH4F. Issue 57 (31st August 2021) - Eisenburger, Lucien; Weippert, Valentin; Oeckler, Oliver; Schnick, Wolfgang
Abstract: Multinary transition metal nitrides and oxonitrides are a versatile and intriguing class of compounds. However, they have been investigated far less than pure oxides. The compounds Sc5 P12 N23 O3 and Ti5 P12 N24 O2 have now been synthesized from the binary nitrides ScN and TiN, respectively, by following a high‐pressure high‐temperature approach at 8 GPa and 1400 °C. NH4 F acts as a mineralizing agent that supports product formation and crystallization. The starting materials ScN and TiN are seemingly an uncommon choice because of their chemical inertness but, nevertheless, react under these conditions. Sc5 P12 N23 O3 and Ti5 P12 N24 O2 crystallize isotypically with Ti5 B12 O26, consisting of solely vertex‐sharing P(O/N)4 tetrahedra forming two independent interpenetrating diamond‐like nets that host TM (O/N)6 ( TM =Sc, Ti) octahedra. Ti5 P12 N24 O2 is a mixed‐valence compound and shows ordering of Ti 3+ and Ti 4+ ions. Abstract : The oxonitridophosphates Sc5 P12 N23 O3 and Ti5 P12 N24 O2 have been prepared by high‐pressure high‐temperature reactions from the refractory nitrides ScN and TiN, respectively. These reactions were enabled by the addition of NH4 F as a mineralizing agent. The crystal structures were elucidated by a combination of SCXRD, BVS calculations and magnetic measurements for Ti5 P12 N24 O2 revealing two distinct crystallographic sites occupied by either Ti 3+ or Ti 4+, respectively.